Actividades lúdicas para la enseñanza de Matemática - Campaña Nieto, Ana Normandy (2016)
Mathematics is a subject that plays a key role in the learning process of students undoubtedly helps develop thinking skills as the child passes to the following grade. At school level mathematics learning is a process that starts the child from an early age and progresses slowly, establishing levels of increasingly formed conceptualization. It is poor implementation of recreational activities in the area of mathematics, when performing the class is a monotonous job and the student does not pay attention, which has caused effects such as school disinterest, therefore this research project is to implement recreational strategies for teachers to apply in their classrooms and motivate the student body care As for the research mode is of field, documentary - descriptive method using a deductive - inductive as well as in the use of research tools such as the interview survey, so that it is proposed a workshop on playful strategies for teachers, thereby causing the motivation to learn and strengthen skills in the importance of mathematics in the teaching - learning process, thus benefiting 30 students and 6 teachers of Fourth Year General Basic Education and indirectly about 120 among students and teachers of the institution.